Immunotherapy Usage Has Not Increased Sub-Lobar Pulmonary Resections Despite Reduced Pneumonectomies - Kelly, A. McGovern; Alex, Watts; Katherine, O. Welch; Giorgos, Karakousis; Wei-Ting, Hwang; Taine, Pechet; Doraid, Jarrar; John, Kucharczak; Jarrod, Predina; Sunil, Singhal (Journal of Lung Cancer Epidemiology, 2026)
Objective The landscape of non-small cell lung cancer (NSCLC) has changed due to liberalized utilization of computed tomography, developments in immunotherapy and targeted treatments, and guidelines encouraging sublobar resections. We analyzed the implications of these advances for surgical procedures over a 16-year period. Methods The National Cancer Database was used to identify NSCLC incident cases from 2004 to 2020. Histology, stage, grade, and treatment were analyzed using descriptive statistics and logistic regression. Results 2,028,553NSCLC patients were identified. Each year was associated with an increase in Stage I for NSCLC (OR1.05, 95%CI 1.05-1.05) and histological subtypes (adenocarcinoma: OR1.03, 95%CI 1.03-1.04; squamous: OR1.02, 95%CI 1.02-1.02; neuroendocrine: OR1.11, 95%CI 1.11-1.12), with no change in adenosquamous histology. A similar increase was observed for well- or moderately-differentiated histology (OR1.04, 95%CI 1.04-1.04). The proportion of patients receiving chemotherapy decreased (OR0.98, 95%CI 0.98-0.98), while more patients were treated with immunotherapy or targeted therapy, including an increase of 14% using immunotherapy or targeted therapy as first-line treatment. There was a decrease in the likelihood of receiving pneumonectomy (OR 0.91, 95%CI 0.91-0.91). Despite guidelines advocating sublobar resections, these procedures only increased by 1.1% per year. Conclusions Over the 16-year study period, there was a significant trend towards diagnosis of Stage I NSCLC. The most pronounced change in treatment patterns has been more patients receiving immunotherapy and less chemotherapy. Despite a promising decrease in pneumonectomies, the frequency of sublobar resections remains stagnant, indicating limited uptage in current practice.
Keywords: Immunotherapy; Sublobar resection; Lung cancer